The Spirit of Sisterhood in Volga’s the Liberation of Sita (International Journal of Food and Nutritional Sciences, 2019)
Volga's The Liberation of Sita is a compelling exploration of the untold stories and voices ofwomen in the epic Ramayana. Within this narrative, the concept of sisterhood emerges as apowerful force, challenging traditional patriarchal norms and giving voice to the suppressedexperiences of women.